Outcome of Stapled Haemorrhoidectomy, A Systematic Review - IMTIAZ HUSSAIN FAROGH ZAHRA AEMER ZAMA, RUKHSANA PERVEEN (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study is to see the outcome of stapled technique of haemorrhoidectomy in terms of operative time and complications like urinary retention and perineal infection. Study Design: Descriptive case series Setting: Department of General Surgery, Unit-I, Sir Ganga Ram Hospital, Lahore. Duration of Study: Six months from 23-May-2011 to 22-December-2011. Subjects and Methods: Two hundreds of patients fulfilling the criteria of study were included in the study. All patients underwent stapled haemorrhoidectomy. They were followed up during early postoperative period i.e. first day after surgery, in first week and at 15 days. Postoperative complications like urinary retention and perineal infection were seen, operative time was noted. Other variable i.e. postoperative bleeding (it is the bleeding with bowel movements during first and second week postoperatively) was also noted. Results: Mean age of patients in study was 46.1±7.9 years. There were 112 (56%) male and 88 (44%) female patients. The mean operative time of the patients was 23.2±3.9 minutes. Postoperative urinary retention was found in 6 (3%) patients. Perineal infection was found in 7 (3.5%) patients and postoperative bleeding was found in 9 (4.5%) patients at 7th postoperative day. No complication was found in any patient at 15th postoperative day. Conclusion: It was concluded from this study that stapled technique of haemorrhoidectomy reduced the operative time and postoperative complications like urinary retention, perineal infection and postoperative bleeding.